An Investigation of Ag/NaTi2(PO4)3 Seawater Battery Toward Scalable Energy Storage - Weng, Guo-Ming (The Global Environmental Engineers, 2024)
The seawater battery, consisted of silver (+ve) and carbon-coated NaTi2(PO4)3 (-ve), is an eco-friendly energy storage system due to the low cost and natural abundance of seawater. However, more efforts are still needed to research on the potential issues associated with the ion transport, the breakdown of voltage losses and the attempts for scaling up of such a battery system. Herein, it is found that a nonnegligible shuttle effect of Ag+ ions could pose a serious impact on the reversibility of the battery system. In addition, through the four-electrode measurement, the carbon-coated NaTi2(PO4)3 negative electrode with intercalation/ deintercalation chemistry is identified as the limiting component in the current battery device. Moreover, attempts on applying semi-solid electrolytes to such a battery system are also conducted. It is found that the capacity fading is serious probably due to the hydrogen evolution side reaction at the negative side. Future technical advancements in the key materials and reactor design will make this battery technology more competitive. This work offers important insights to develop safer and scalable seawater batteries.